Pericardial complications of endocardial and epicardial pacing. Issue 6292 (5th September 1981) - Deanfield, J; Jonathan, A; Fox, K
Abstract : A patient with complete atrioventricular block was fitted with a temporary endocardial pacing wire via a right subclavian percutaneous approach. The result was initially satisfactory, but within a few days radiography for left-sided chest pain showed pneumopericardium. A permanent epicardial pacing system was therefore substituted and she remained well for three months. She was then admitted for syncope: the pacemaker was failing to capture, and radiography showed pericardial and pleural effusion. A new permanent endocardial pacing system using a wedged electrode was inserted and she made an uncomplicated recovery. Pneumopericardium complicating endocardial pacing has apparently not been reported before. Presumably the electrode had penetrated both the right ventricle and the pericardium into the adjacent lung.